Recent Insight on the Non-coding RNAs in Mesenchymal Stem Cell-Derived Exosomes: Regulatory and Therapeutic Role in Regenerative Medicine and Tissue Engineering - Pant, Tarun; Juric, Matea; Bosnjak, Zeljko J.; Dhanasekaran, Anuradha (Frontiers in Cardiovascular Medicine, 2021)
Advances in the field of regenerative medicine and tissue engineering over the past few decades have paved the path for cell-free therapy. Numerous stem cell types, including mesenchymal stem cells (MSCs), have been reported to impart therapeutic effects via paracrine secretion of exosomes. The underlying factors and the associated mechanisms contributing to these MSC-derived exosomes' protective effects are, however, poorly understood, limiting their application in the clinic. The exosomes exhibit a diversified repertoire of functional non-coding RNAs (ncRNAs) and have the potential to transfer these biologically active transcripts to the recipient cells, where they are found to modulate a diverse array of functions. Altered expression of the ncRNAs in the exosomes has been linked with the regenerative potential and development of various diseases, including cardiac, neurological, skeletal, and cancer. Also, modulating the expression of ncRNAs in these exosomes has been found to improve their therapeutic impact. Moreover, many of these ncRNAs are expressed explicitly in the MSC-derived exosomes, making them ideal candidates for regenerative medicine, including tissue engineering research. In this review, we detail the recent advances in regenerative medicine and summarize the evidence supporting the altered expression of the ncRNA repertoire specific to MSCs under different degenerative diseases. We also discuss the therapeutic role of these ncRNA for the prevention of these various degenerative diseases and their future in translational medicine.